2019
DOI: 10.1097/md.0000000000016404
|View full text |Cite
|
Sign up to set email alerts
|

Fruits and vegetables consumption and the risk of gallstone diasease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Overall, the combined RR was 0.83 (95% CI 0.76–0.89), and each additional cup of coffee consumed per day was associated with a 5% (RR = 0.95, 95% CI 0.91–1.00, p = 0.049) reduction in cholecystolithiasis risk. As for the relationship between vegetable and fruit consumption and cholecystolithiasis, current evidence suggests that vegetable consumption is associated with a 17% (RR = 0.83, 95% CI 0.74–0.94) lower risk and fruit with a 12% (RR = 0.83, 95% CI 0.83–0.92) lower risk [ 40 ]. Moreover, there is a dose–response relationship between the intake of vegetables and fruits and the risk of disease, that is, for each additional 200 g per day, the corresponding risk of disease will be reduced by 4% (RR = 0.96, 95% CI 0.93–0.98, p = 0.001) and 3% (RR = 0.97, 95% CI 0.96–0.98, p = 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the combined RR was 0.83 (95% CI 0.76–0.89), and each additional cup of coffee consumed per day was associated with a 5% (RR = 0.95, 95% CI 0.91–1.00, p = 0.049) reduction in cholecystolithiasis risk. As for the relationship between vegetable and fruit consumption and cholecystolithiasis, current evidence suggests that vegetable consumption is associated with a 17% (RR = 0.83, 95% CI 0.74–0.94) lower risk and fruit with a 12% (RR = 0.83, 95% CI 0.83–0.92) lower risk [ 40 ]. Moreover, there is a dose–response relationship between the intake of vegetables and fruits and the risk of disease, that is, for each additional 200 g per day, the corresponding risk of disease will be reduced by 4% (RR = 0.96, 95% CI 0.93–0.98, p = 0.001) and 3% (RR = 0.97, 95% CI 0.96–0.98, p = 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, consumption of fruits and vegetables should also be preferred because, according to Ansari-Moghaddam, low consumption of fruit and vegetables would increase the risk of cholelithiasis by twice (OR, 2.51; 95% CI, 1.29 -4.88) [20]. And one study about the dose-response correlation indicated that gallstone risk was reduced by 3% and 4% for every 200 g per day increment in fruits and vegetables consumption [8]. A nonvegetarian diet and hypercholesterolemia may have an additive effect in increasing GSD risk in women.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that the presence of gallstones increases with age and that predisposing risk factors for gallstone formation include obesity, diabetes mellitus, estrogen and pregnancy, hemolytic diseases and cirrhosis [6]. Furthermore, diet can be a modifiable risk factor to prevent gallstone disease [7][8][9]. And in our country, despite the impact of globalization on dietary habits and lifestyle, the Malagasy culture keeps its features.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced risks of chronic obstructive pulmonary disease ( 33 ) and gallstone disease ( 34 ) have also been reported; however, the latter also included case-control studies and cross-sectional studies ( 34 ). Inverse associations between the intake of fruits and vegetables and the risk of inflammatory bowel disease (Crohn’s disease and ulcerative colitis) are also indicated ( 35 , 36 ), of which one report was based on case-control studies only ( 36 ).…”
Section: Health Outcomes Relevant For Nordic and Baltic Countriesmentioning
confidence: 99%